2011
DOI: 10.1007/s11664-011-1723-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Dislocations in Single-Crystal SrTiO3 Substrates by Electron Channeling

Abstract: Electron channeling contrast imaging (ECCI) using a conventional polemounted backscatter detector in a commercial scanning electron microscope (SEM) has been implemented to analyze extended defects. In-grown extended defects in bulk SrTiO 3 (001) substrates such as dislocation loops, subsurface dislocations parallel to the surface, and surface-penetrating dislocations have been distinguished by ECCI. The techniques of dislocation-selective etching and ECCI have been compared side-by-side, where surface-penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…6(e)). Transmission and scanning electron microscopy studies of selectively etched single crystal SrTiO 3 revealed dislocation densities of ∼10 8 cm −2 [140,141], qualitatively in agreement with the observed disorder fluctuations. The ability to non-invasively identify these very localised features at the domain walls could be especially interesting when coupled with an investigation of their functional properties [74].…”
Section: Towards More Complex Physics At Domain Wallssupporting
confidence: 79%
“…6(e)). Transmission and scanning electron microscopy studies of selectively etched single crystal SrTiO 3 revealed dislocation densities of ∼10 8 cm −2 [140,141], qualitatively in agreement with the observed disorder fluctuations. The ability to non-invasively identify these very localised features at the domain walls could be especially interesting when coupled with an investigation of their functional properties [74].…”
Section: Towards More Complex Physics At Domain Wallssupporting
confidence: 79%
“…X-ray diffraction (XRD) provides averages over a large scale and requires significant calibration. Electron channeling contrast imaging (ECCI), however, offers a straightforward and non-destructive way to image extended defects over micron length scales; recent examples include dislocation imaging in semiconductors (GaN) [1] and perovskite oxides (SrTiO 3 ) [2].In this study, ECCI is employed to investigate defects associated with misfit strains in epitaxial La 0.7 Sr 0.3 MnO 3 (LSM) thin films. LSM adopts the perovskite structure and possesses many interesting properties, such as ferromagnetism, colossal magnetic resistance (CMR), and excellent oxygen exchange properties for solid oxide fuel cell (SOFC) cathodes.…”
mentioning
confidence: 99%
“…X-ray diffraction (XRD) provides averages over a large scale and requires significant calibration. Electron channeling contrast imaging (ECCI), however, offers a straightforward and non-destructive way to image extended defects over micron length scales; recent examples include dislocation imaging in semiconductors (GaN) [1] and perovskite oxides (SrTiO 3 ) [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29) and SrTiO 3 . 30 In ECCI, images are produced from electrons which channel down the crystal planes of a suitably oriented sample. Changes in crystallographic orientation, or in lattice constant due to local strain, are revealed by changes in contrast in a channeling image constructed by monitoring the intensity of backscattered electrons as the electron beam is scanned over the sample.…”
mentioning
confidence: 99%